Pembelajaran SBdP pada Materi Karya Seni Anyaman untuk Mengembangkan Kreativitas Siswa Sekolah Dasar - Ema Zulfiani; Wasis Wijayanto (Journal on Education, 2025)
This study aims to describe the process of learning Arts, Culture, and Crafts (SBdP) on the subject of woven artwork and analyze how these activities can develop students' creativity in elementary schools. The research method used is descriptive qualitative. Data were obtained through observation, interviews, and documentation. The study was conducted at SD Negeri 4 Prambatan Kidul with a fifth-grade teacher and all fifth-grade students, totaling 25 people. This study serves to determine how SBdP learning develops the creativity of elementary school children. The results show that SBdP learning on woven artwork material is implemented through several stages, namely explaining basic concepts, introducing woven motifs, showing videos of the weaving process, and direct practice using paper materials. Students showed high enthusiasm, actively asked questions, and produced works with a variety of motifs and colors. Practice-based and visual learning helps students understand art concepts concretely which can foster creativity. Thus, SBdP learning on woven material can be an effective means to foster creativity, imagination, and fine motor skills in elementary school students.